(untitled) (Medico Legal Update, 2020)
A descriptive study to assess the risk factors of obesity among housewives residing at selected community, setting in Kanchipuram District, Tamil Nadu. The objectives were to assess the risk factors of obesity among the housewives to find out the association between assess the risk factors of obesity and selected demographic data of obesity among the house wives. A non – experimental, descriptive study was conducted. The sampling technique was non-probability, purposive sampling technique with the sample of 30 housewives among obesity and Structured questionnaires (SQ) in the form was used to the assess the risk factors obesity among housewives. The variables were assessed the assess the risk factors of obesity among housewives. Hypotheses were formulated. The level of significance selected was p<0.05. The investigator used demographic data and Structured questionnaires (SQ) was used to collect data. The data collection for the main study was done . The collected data was tabulated and analysed. Descriptive and inferential statistical were used. The mean value was 207 and the standard deviation was 2.8133. The study shows that the risk factors of obesity inadequate 7 (23%) were moderate 21(70%) and adequate was 2 (7%). The study concludes that there is moderate 70% to assess the risk factors of obesity among housewives.